The Joint Effects of Income, Vehicle Technology, and Rail Transit Access on Greenhouse Gas Emissions. Issue 24 (December 2018) - Boarnet, Marlon G.; Bostic, Raphael W.; Eisenlohr, Andrew; Rodnyansky, Seva; Santiago-Bartolomei, Raúl; Jamme, Huê-Tâm Webb
This paper examines the relationship between income, vehicle miles traveled (VMT), and greenhouse gas (GHG) emissions for households with varying access to rail transit in four metropolitan areas—Los Angeles, the San Francisco Bay Area, San Diego, and Sacramento—using data from the 2010–2012 California Household Travel Survey. Daily vehicle GHG emissions are calculated using the California Air Resources Board's 2014 EMFAC (emission factors) model. Two Tobit regression models are used to predict daily VMT and GHG by income, rail transit access (within or outside 0.5 miles of a rail transit station in Los Angeles and the Bay Area, and linear distance to rail in San Diego and Sacramento), and metropolitan area. Comparing predicted VMT and GHG emissions levels, this paper concludes that predicted VMT and GHG emission patterns for rail access vary across metropolitan areas in ways that may be related to the age and connectivity of the areas' rail systems. The results also show that differences in household VMT due to rail access do not scale proportionally to differences in GHG emissions. Regardless, the fact that GHG emissions are lower near rail transit for virtually all income levels in this study implies environmental benefits from expanding rail transit systems, as defined in this paper.